Associativity in Inheritance or are there Associative Populations? - Ganikhodjaevl, Nasir ’ (Malaysian Journal of Science, 2008)
An algebraic structure naturally occurs as genetic information gets passed down through the generations. The existence of associative algebras with genetic realization is proved.